The reduction of oxygen in various room temperature ionic liquids in the temperature range 293-318 K: exploring the applicability of the Stokes-Einstein relationship in room temperature ionic liquids. - Huang, X; Rogers, E; Hardacre, C; Compton, R (2009)
The voltammetry for the reduction of oxygen at a microdisk electrode is reported in six commonly used RTILs: [C(4)mim][NTf(2)], [C(4)mpyrr][NTf(2)], [C(4)dmim][NTf(2)], [C(4)mim][BF(4)], [C(4)mim][PF(6)], and [N(6,2,2,2)][NTf(2)], where [C(4)mim](+) is 1-butyl-3-methylimidazolium, [NTf(2)](-) is bis(trifluoromethanesulfonyl)imide, [C(4)mpyrr](+) is N-butyl-N-methylpyrrolidinium, [C(4)dmim](+) is 1-butyl-2,3-methylimidazolium, [BF(4)](-) is tetrafluoroborate, [PF(6)](-) is hexafluorophosphate, and [N(6,2,2,2)](+) is n-hexyltriethylammonium at varying scan rates (50-4000 mV s(-1)) and temperatures (293-318 K). Diffusion coefficients, D, of oxygen are deduced at each temperature from potential-step chronoamperometry, and diffusional activation energies are calculated. Oxygen solubilities are also reported as a function of temperature. In the six ionic liquids, the Stokes-Einstein relationship (D proportional, variant eta(-1)) was found to apply only very approximately for oxygen. This is considered in relationship to the behavior of other diverse solutes in RTILs.